Subject and Subjectivity in Historical Thought : Some Comments on Recent Methodology of History and Archival Studies - Čtvrtník, Mikuláš (Dějiny – teorie – kritika, 2015)
The author analyses the position of subject and subjectivity in historical thought. The aim of the investigation is to describe in detail the various ways in which the role of the cognising subject and the nature of subjectivity have been approached in debates about the methodology of history in the 20th century. The author also offers some insights on the current discussion about subjectivity in historical science and related areas of archival theory, methodology, and practice.